Aspergillus niger Decreases Bioavailability of Arsenic(V) via Biotransformation of Manganese Oxide into Biogenic Oxalate Minerals - Farkas, Bence; Kolenčík, Marek; Hain, Miroslav; Dobročka, Edmund; Kratošová, Gabriela; Bujdoš, Marek; Feng, Huan; Deng, Yang; Yu, Qian; Illa, Ramakanth; Sunil, B Ratna; Kim, Hyunjung; et al. (Journal of fungi (Basel, Switzerland), 2020)
The aim of this work was to evaluate the transformation of manganese oxide (hausmannite) by microscopic filamentous fungus Aspergillus niger and the effects of the transformation on mobility and bioavailability of arsenic. Our results showed that the A. niger strain CBS 140837 greatly affected the stability of hausmannite and induced its transformation into biogenic crystals of manganese oxalates-falottaite and lindbergite. The transformation was enabled by fungal acidolysis of hausmannite and subsequent release of manganese ions into the culture medium. While almost 45% of manganese was bioextracted, the arsenic content in manganese precipitates increased throughout the 25-day static cultivation of fungus. This significantly decreased the bioavailability of arsenic for the fungus. These results highlight the unique A. niger strain's ability to act as an active geochemical factor via its ability to acidify its environment and to induce formation of biogenic minerals. This affects not only the manganese speciation, but also bioaccumulation of potentially toxic metals and metalloids associated with manganese oxides, including arsenic.
Keywords: bioextraction; bioaccumulation; filamentous fungi; arsenic; manganese minerals